Analysis of the Impact of Environmental Criminal Law Enforcement on Environmental Pollution Perpetrators (Case Study of Waste Pollution in the City) - Sandra, Gustika; Rasyid, Mukhawas; Agustapa, Agustapa; Suriyati, Suriyati (Journal of Public Representative and Society Provision, 2025)
The main problem of discussion is what factors are the enforcement of environmental criminal law against perpetrators of environmental pollution violations. This type of research is normative research, writing using a legislative approach, namely Law Number 32 of 2009 concerning Environmental Protection and Management. This research uses a data collection method through library studies, data is collected by quoting, analyzing using content analysis of literature that is relevant to the problem discussed, namely the enforcement of environmental criminal law against perpetrators of environmental pollution. The results of the study obtained law enforcement factors seen from pollution actions, environmental damage, non-compliance, significant negative impacts on the environment and health and also environmental criminal sanctions in the form of administrative fines such as warnings to revocation of business permits and severe criminal sanctions against perpetrators. Enforcement of environmental criminal law against perpetrators of pollution has an important influence in efforts to protect the environment and prevent further damage. The deterrent effect provided by criminal sanctions is expected to increase awareness and responsibility of perpetrators towards the environment. In addition, criminal law enforcement also helps ensure that perpetrators are responsible for their actions and recover the losses that have been caused.